2005
DOI: 10.1097/01.don.0000140573.72922.c9
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Heat Generation Using Ultrasonic Vibration for Post Removal

Abstract: This study measured the temperature of the root surface and post during the application of ultrasonic vibration to cemented posts to simulate post removal procedure. Root canal therapy was performed on ten extracted maxillary incisors. A stainless steel Parapost was cemented into each prepared post space. Ultrasonic vibration was applied to the post and temperatures were recorded at the coronal post and the cervical root surface. Data were analyzed with ANOVA using the independent variables of (a) time of ultr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
48
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 20 publications
5
48
0
Order By: Relevance
“…Our results are in accordance with observations made by Kumar et al, 12 Lolayekar et al 10 and Dominici et al, 13 who also observed 10% formalin, 5.25% sodium hypochlorite and autoclaving were the best methods of sterilization. These procedures did not seem to affect the "feel" and cutting characteristics of the teeth.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our results are in accordance with observations made by Kumar et al, 12 Lolayekar et al 10 and Dominici et al, 13 who also observed 10% formalin, 5.25% sodium hypochlorite and autoclaving were the best methods of sterilization. These procedures did not seem to affect the "feel" and cutting characteristics of the teeth.…”
Section: Discussionsupporting
confidence: 93%
“…These procedures did not seem to affect the "feel" and cutting characteristics of the teeth. 13,14 However, a study by Abdul-Rahman et al 15 showed that the immersion of the extracted teeth for 7 days in 2.5% sodium hypochlorite, autoclaving at 121 C, 15 lbs for 15 min and the use of the microwave for 6 or 3 min were effective in disinfecting the extracted human teeth. In the present study, formalin, 5.25% sodium hypochlorite and autoclaving were more effective than other chemical and physical methods for sterilization and disinfection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It appears that in vivo root surface temperature rises may be lower because of periodontal ligament, bone and microvasculature (21,26,30). Despite this, the relatively high temperature rises recorded on the root surface of mandibular incisors suggest however that caution should be exercised when using the high-temperature thermoplasticized injectable gutta-percha obturation technique to fill the teeth with thin remaining root dentin.…”
Section: Discussionmentioning
confidence: 99%
“…1 It is also possible that the thermal cycling may cause teeth with amalgam restorations to fracture due to their differences in coefficient of thermal expansion. 13 Infection control guidelines for use of extracted teeth in dental educational settings: 2 Extracted teeth used for the education of dental health care workers should be considered infective and classified as clinical specimens because they contain blood.…”
Section: A Comparison Of Different Methods For Disinfection or Sterilmentioning
confidence: 99%